2009
DOI: 10.3332/ecancer.2009.128
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of c-Myc oncoprotein in oral squamous cell carcinoma

Abstract: Oral neoplasm constitutes a predominant class of cancer that is encountered in South India. This is in large part due to the elevated risk of oncogenesis as a result of the habit of chewing of quids containing betel leaves, areca nut and smokeless tobacco. An array of molecular events are induced during the transformation of the buccal epithelium, among them the over-expression of oncogene products plays a key role. The c-Myc protein, a regulator of a number of key cellular signalling pathways, plays a pivotal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…C-myc or myc gene was the first to be discovered in this family and is persistently expressed in many different types of cancer, including head and neck squamous cell carcinoma (HNSCC). A number of studies of the molecular mechanisms underlying oncogenesis have shown the emergence of c-Myc expression as a key event, and it is frequently overexpressed in oral cancers as a consequence of gene amplification 4 . C-myc overexpression is responsible for poor tumor prognosis 5 – 8 as well as the self-renewal of tumor stem cells 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…C-myc or myc gene was the first to be discovered in this family and is persistently expressed in many different types of cancer, including head and neck squamous cell carcinoma (HNSCC). A number of studies of the molecular mechanisms underlying oncogenesis have shown the emergence of c-Myc expression as a key event, and it is frequently overexpressed in oral cancers as a consequence of gene amplification 4 . C-myc overexpression is responsible for poor tumor prognosis 5 – 8 as well as the self-renewal of tumor stem cells 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Cytokeratin 5 is commonly used as an immunohistochemical marker for squamous cell carcinomas [48]. However, although c-Myc is often expressed in those tumor types, it is not known to be a specific marker for squamous cell carcinomas and has been detected in other tumor types before [49][50][51][52]. The expression of these proteins might not only be useful for diagnostic purposes but could further insight into the tumor's biology and indicate potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%